Dissemination of Evidence‐Based Antipsychotic Prescribing Guidelines to Nursing Homes: A Cluster Randomized Trial. Issue 7 (14th July 2015) - Tjia, Jennifer; Field, Terry; Mazor, Kathleen; Lemay, Celeste A.; Kanaan, Abir O.; Donovan, Jennifer L.; Briesacher, Becky A.; Peterson, Daniel; Pandolfi, Michelle; Spenard, Ann; Gurwitz, Jerry H.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the effectiveness of efforts to translate and disseminate evidence‐based guidelines about atypical antipsychotic use to nursing homes (NHs). Design Three‐arm, cluster randomized trial. Setting NHs. Participants NHs in the state of Connecticut. Measurements Evidence‐based guidelines for atypical antipsychotic prescribing were translated into a toolkit targeting NH stakeholders, and 42 NHs were recruited and randomized to one of three toolkit dissemination strategies: mailed toolkit delivery (minimal intensity); mailed toolkit delivery with quarterly audit and feedback reports about facility‐level antipsychotic prescribing (moderate intensity); and in‐person toolkit delivery with academic detailing, on‐site behavioral management training, and quarterly audit and feedback reports (high intensity). Outcomes were evaluated using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE‐AIM) framework. Results Toolkit awareness of 30% (7/23) of leadership of low‐intensity NHs, 54% (19/35) of moderate‐intensity NHs, and 82% (18/22) of high‐intensity NHs reflected adoption and implementation of the intervention. Highest levels of use and knowledge among direct care staff were reported in high‐intensity NHs. Antipsychotic prescribing levels declined during the study period, but there were no statistically significant differences between study arms or from secular trends. Conclusion RE‐AIM indicators suggest some success in disseminating the toolkit and differences in reach, adoption, and implementation according to dissemination strategy but no measurable effect on antipsychotic prescribing trends. Further dissemination to external stakeholders such as psychiatry consultants and hospitals may be needed to influence antipsychotic prescribing for NH residents.